Code Mixing Found in Bukan Empat Mata Program on Trans 7 Television Channel - Hamidah, Fitria Nur (JEELS (Journal of English Education and Linguistics Studies), 2015)
This study is aimed to find the kinds of code mixing and to know which kinds of code mixing are dominantly used in Bukan Empat Mata Program on TRANS 7 Television channel. Descriptive qualitative method is used in this study. The data were collected through watching, recording, transferring, playing, selecting and transcribing the data from the conversations between the presenters and the guest stars. The collected data were then analyzed through identifying the data, selecting the data related to the code mixing, listing and classifying the data based on the kinds of code mixing and finally drawing conclusion. It was found that there are two kinds of code mixing used by prersenters and guest stars in Bukan Empat Mata program, namely situational and conversational code mixing. Between two kinds of code mixing, conversational code mixing is dominantly used both by presenters and the guest stars in which they sometimes change the pronunciation from English into Indonesian in the conversation.